The neighborhood as an energy-generating community: the case of the El Banafseg residential neighborhood, East Cairo - Helmy, Mona; Micheal, Amany (Frontiers in Built Environment, 2023)
Nowadays, energy consumption is a global challenge due to the shortage of some energy sources and, consequently, their increasing prices. This paper argues that by using an integrative approach for using various energy harvesting techniques, a typical residential neighborhood can be operated as a self-generator of some or all of its needed energy. The paper follows mixed qualitative, experimental, and numerical simulation approaches to examine the practicality of the hypothesis. It uses Space syntax modeling theory (socio-spatial software) to analyze the pedestrian flow to indicate potential locations of kinetic energy harvesting piezoelectric tiles in the selected residential neighborhood. In addition, the possibility of installing photovoltaic electrical cells on rooftops of the neighborhood residential blocks is studied. The numerical simulation quantifies the capacity of the harvested energy to achieve a model of a green neighborhood. The paper measures the percentage of the residences’ energy needs that can be harvested using renewable energy resources. It reveals that 30% of the energy consumed in the residential blocks can be generated from photovoltaic electrical cells, and 38% of the energy consumed by street lighting of the entire neighborhood could be generated using the kinetic energy harvested by piezoelectric tiles.